Efektivitas Pemberian Buah Kurma Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Dengan Anemia - Ayunda Sinta Sumitran (Pusat Riset dan Inovasi Nasional, 2023)
Background: Anemia in pregnant women when the hemoglobin level is below 11gr/dL. Dates are one of the non-pharmacological therapies in the treatment of anemia. Research objective: to determine the effectiveness of giving dates to increase hemoglobin levels in anemic pregnant women. Research method: This research design uses experimental methods. In this study using the research design Two Group Pre test Post test Control Design. The population in this study were all pregnant women at the Independent Midwife Practice, a total of 50 people who experienced anemia. The sample studied was 20 pregnant women who experienced anemia. The experimental group was given 7 dates of dates every day for 7 days and the control group only consumed Fe tablets. Results: The average value of hemoglobin levels in the pretest control group was 10.090 ± 5685 gr/dl while the posttest was 10.210 ± 0.4999 gl/dl. The average value of hemoglobin levels in the pretest treatment group was 10.100 ± 0.6360 gl/dl while the posttest was 11.310 ± 0.7608 gl/dl. The Mann Witney test showed that the difference in hemoglobin levels between the treatment group and the case group resulted in a p value of 0.004 <0.005, which means that there was a difference in the results of hemoglobin levels between the dates given group and the case group. Conclusion: dates are effective in increasing hemoglobin levels in anemic pregnant women.